2014
DOI: 10.1007/s11916-014-0428-1
|View full text |Cite
|
Sign up to set email alerts
|

Medication Overuse in Children and Adolescents

Abstract: Medication overuse is not uncommon among children and adolescents with primary headache disorders. In adults, medication overuse is associated with increased headache frequency and reduced effectiveness of acute and preventive medications. These issues may also exist in children. While withdrawal of overused medications is generally recommended, it may not result in improved headache frequency in all patients. This review summarizes what is known about predicting response to medication withdrawal. Strategies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 42 publications
3
36
1
1
Order By: Relevance
“…Lower headache frequency per month was significantly associated with a better clinical response in patients with episodic headache but not chronic headache. Although the adverse effect of overuse of medication on treatment response in our study was not significant, the achievement of a P value equal to .05 may suggest a trend, consistent with earlier studies showing that medication overuse is an important cause of chronic migraine and associated with lower efficacy of migraine preventive medication …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Lower headache frequency per month was significantly associated with a better clinical response in patients with episodic headache but not chronic headache. Although the adverse effect of overuse of medication on treatment response in our study was not significant, the achievement of a P value equal to .05 may suggest a trend, consistent with earlier studies showing that medication overuse is an important cause of chronic migraine and associated with lower efficacy of migraine preventive medication …”
Section: Discussionsupporting
confidence: 90%
“…Although the adverse effect of overuse of medication on treatment response in our study was not significant, the achievement of a P value equal to .05 may suggest a trend, consistent with earlier studies showing that medication overuse is an important cause of chronic migraine and associated with lower efficacy of migraine preventive medication. 17,18 We found no association between migraine with or without aura and treatment response. By contrast, a study in adults reported a lesser effect of sumatriptan as acute therapy for migraine attacks with aura than without aura.…”
Section: Discussioncontrasting
confidence: 53%
“…Chiappedi and Balottin [Chiappedi and Balottin, 2014], and Gelfand and Goadsby [Gelfand and Goadsby, 2014] recently reviewed the literature on MOH in children and adolescents and showed that population-based epidemiologic studies are sparse (with data available only from Norway, Taiwan, and the US) but MOH is commonly encountered in the clinical setting.…”
Section: Population Prevalence Of Mohmentioning
confidence: 99%
“…There is disagreement on how to discontinue medication (gradual reduction versus complete withdrawal); and when to use preventive medication (early in the treatment period or after medication reduction). There is sparse data on best practice for the treatment of MOH in children [Gelfand and Goadsby, 2014]. Comorbidity MOH has been linked to comorbid psychiatric disorders [Atasoy et al 2012;Fuh and Wang, 2012;Radat and Lanteri-Minet, 2012].…”
Section: Treatment Protocolmentioning
confidence: 99%
“…The age span is 3-18 years depending on the disorder. The main consequences of frequent headaches in children and adolescents are more frequent school absences; disturbed health-related quality of life (HRQOL) [5] and a risk of medication overuse [6].…”
Section: Introductionmentioning
confidence: 99%